Jordan Student Assessment : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2017)
SABER-Student Assessment is a component of the SABER program that focuses specifically on benchmarking studentassessment policies and systems. The goal of SABER-Student Assessment is to promote stronger assessment systems that contribute to improved education quality and learning for all. Jordan has focused on increasing student learning outcomes by improving the quality of education in the country. An effective student assessment system is an important component to improving education quality and learning outcomesas it provides the necessary information to meet stakeholders’ decision-making needs. In order to gain a better understanding of the strengths and weaknesses of its existing assessment system, Jordan decided to benchmark this system using standardized tools developed under the World Bank’s Systems Approach for Better Education Results(SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The SABER-Student Assessment framework is built on the available evidence base for what an effective assessment system looks like. The framework provides guidance on how countries can build more effective student assessment systems. The framework is structured around two main dimensions of assessment systems: the types/purposes of assessment activitiesand the quality of those activities. The key policy areas for this student assessment status are as follows: (i) Classroom Assessment; (ii) Examinations; (iii) National Large-Scale Assessment (NLSA); and (iv) International Large-Scale Assessment (ILSA).